Pengaruh Corporate Social Responsibility terhadap Nilai Perusahaan dengan Good Corporate Governance sebagai Pemoderasi - Olvianda, Ilmi; Serly, Vanica (Universitas Negeri Padang, 2025)
This study aims to examine the effect of Corporate Social Responsibility on Company Value with Good Corporate Governance as a moderating variable. This study is included in the type of research with a quantitative approach. The population includes basic material companies listed on the Indonesia Stock Exchange in 2018-2022. The sampling technique was carried out using the purposive sampling method, there were 38 companies from 2018 to 2022 that were the samples of this study. The Company Value variable as the dependent variable is measured by Tobin's q. Corporate social responsibility as an independent variable, is measured by content analysis or dummy by weighting. If the indicator item is disclosed, it is given the number 1, but if the indicator item is not disclosed it will be given the number 0. The hypothesis was tested using moderated regression analysis with SPSS. The results showed that Corporate social responsibility has a positive and significant effect on Company Value and Good Corporate Governance cannot strengthen the relationship between Corporate social responsibility and Company Value. Further research can consider including additional variables or expanding the population in order to gain broader insights.